Peningkatan Resapan Air Tanah dengan Saluran Resapan dan Rorak untuk Meningkatkan Produktivitas Belimbing Manis (Studi Kasus di Kota Depok) - Yanto Surdianto; Budi Indra Setiawan; Prastowo Prastowo; Satyanto Krido Saptomo (Balai Teknik Irigasi, 2012)
Problem faced by star fruit farmers in Depok, West Java, is water availability relying only on rainfed. Therefore, research related to water conservation technique for optimum utilization of rain water and runoff at the starfruit orchard was conducted. The objectives of the research were: 1) The relationship between rainfall, evapotranspiration with starfruit productivity, 2) To find out the effects of soil water absoption on starfruit productivity , and 3) To develope water balance analytical model without runoff for sweet starfruit orchard. In this experiment the water table was approximately 16 m from soil surface, no irrigation was used and water storage canals equipped with silt pits were constructed so that runoff component and contribution of water capillarity movement were zero. The research results showed that: 1) The rainfall and evapotranspiration had influence on the starfruit productivity; 2) The relatively high rainfall followed by high soil water content at the rooting zone, ranging from 0,429 to 0,458 m3/m3, enabled the star fruit to have year-round production with four times harvesting; 3) The water balance analytical model without runoff could nicely simulate the soil water content at the rooting zone with R2 of 0,83.